English learning model based on social media - Imron, Aly; Wahyuni, Erly; Mandang, Selvie Ratna Ivone; Mustain, Kun; Susanto, Budi (Politeknik Negeri Bali, 2023)
This research endeavours to address the pressing need for a tailored English language learning model for students enrolled in Polytechnic institutions specializing in Food and Beverage studies. Recognizing the pivotal role of English proficiency in global culinary communication, we aim to design a comprehensive learning model. This model harnesses the potential of social media as an innovative pedagogical tool to enhance language skills, equipping students with the linguistic competence essential for success in their field. A mixed-methods approach was employed, combining quantitative and qualitative research methodologies. Initially, a thorough needs analysis was conducted to determine the specific language requirements of Food and Beverage students. Subsequently, an adaptive learning model was designed, incorporating social media platforms as supplementary tools for language acquisition. The model was tested within the curriculum of a Polytechnic institution, utilizing a pre-test/post-test design to assess the impact on students' language proficiency. The results of our study indicate a significant improvement in the English language proficiency of students following the implementation of the learning model. Quantitative analysis of pre-test and post-test scores revealed a statistically significant increase in language skills. Moreover, qualitative feedback from students and educators highlighted the model's efficacy in enhancing engagement and motivation, thereby fostering a more dynamic and effective learning environment. This research contributes to the intersection of language education and the Food and Beverage industry by providing a specialized English language learning model. The innovative integration of social media platforms as supplementary tools demonstrates the adaptability and effectiveness of this approach. The findings affirm the model's potential to bridge the gap between industry-specific language requirements and educational curricula, empowering students with the linguistic competence necessary for global success in the Food and Beverage sector. This study underscores the transformative potential of technology-enhanced language learning in specialized fields and lays the foundation for future research and pedagogical innovation. Ultimately, this research seeks to empower students, educators, and the industry at large, enriching the landscape of culinary education and communication on a global scale.